Atlas of Ultrasonography in Urology, Andrology, and Nephrology - Martino, Pasquale; Galosi, Andrea B. (Springer International Publishing : Imprint: Springer, 2017)
This book provides the latest recommendations for ultrasound examination of the entire urogenital system, particularly in the male. The coverage encompasses the role of ultrasound in imaging of disorders of the kidneys, urinary tract, prostate, seminal vesicles, bladder, testes, and penis, including male infertility disorders. In addition, detailed consideration is given to intraoperative and interventional ultrasound and recently developed ultrasound techniques. Each chapter defines the purpose of and indications for ultrasound, identifies its benefits and limitations, specifies the technological standards for devices, outlines performance of the investigation, establishes the expected accuracy for differential diagnosis, and indicates the reporting method. Most of the recommendations are based on review of the literature, on previous recommendations, and on the opinions of the experts of the Imaging Working Group of the Italian Society of Urology (SIU) and the Italian Society of Ultrasound in Urology, Andrology, and Nephrology (SIEUN). The book will be of value for all physicians involved in the first-line evaluation of diseases of the renal/urinary system and male genital disorders.